The regional emergence of innovative start-ups: A research agenda - Michael Fritsch (Friedrich Schiller University Jena, 2018)
This paper reviews the empirical evidence concerning the regional emergence of innovative new businesses. It is argued that analyses using aggregate data that focus on the regional level and do not account for career patterns of innovative founders are of limited value in guiding policy that is aimed at fostering the emergence of innovative new businesses. Progress can be mainly expected from research that investigates the family backgrounds, education, and employment careers of potential founders. Moreover, it would be helpful to develop clearer empirical definitions of what constitutes an innovative new business, and the distinctions between different types of innovative businesses.
Keywords: L26; D22; O31; R12; R30; 330; innovative start-ups; universities; employment career